A novel microplate-based HPLC-fluorescence assay for determination of NADPH-cytochrome P450 reductase activity - Erban, Tomas; Poltronieri, Palmiro; Stara, Jitka (Biomedical chromatography, 2012)
A 96-well microplate-based HPLC endpoint assay is described for the determination of NADPH-cytochrome P450 reductase (CPR) activity. Novel sampling of NADPH into microplates was optimized. Separation was performed on a Zorbax Eclipse XDB-C₁₈ analytical 4.6 × 150 mm, 5 µm column. To validate the method, recombinant human NADPH-P450 reductase and microsomes with cytochrome P450 CYP1A1 were used. The mobile phase consisted of 80% acetonitrile and 20% water at a flow-rate of 0.8 mL/min. The CPR activity was quantified using NADPH fluorescence at λ(Ex) = 340 nm and λ(Em) = 450 nm. Enzymatic activity was directly proportional to the decrease in NADPH fluorescence. This analytical process enables a highly sensitive endpoint determination for reductase activity in vitro and monitoring of the consumption of NADPH in enzymatic reactions. The method avoids the use of substrates and of organic solvents that may affect CPR and cytochrome P450 activity. In the reaction, molecular oxygen served as a proton source. The method can substitute spectrophotometric detection methods for its accuracy, high reproducibility (~100%) and sensitivity. The lower limit of detection, shown using the Agilent 1200 aparatus, is in the 250 nmol range. In addition, using this method it is possible to set up reactions in a high-throughput format.
Keywords: NADP; Reproducibility of Results; fluorescenční spektrometrie; reprodukovatelnost výsledků; kalibrace; acetonitrily; rekombinantní proteiny; lineární modely; Limit of Detection; limita detekce; Chromatography, High Pressure Liquid; NADPH-Ferrihemoprotein Reductase; vysokoúčinná kapalinová chromatografie; Acetonitriles; Linear Models; Spectrometry, Fluorescence; Calibration; NADPH-cytochrom c-reduktasa; Humans; lidé; Recombinant Proteins